IMPROVING HUMAN RESOURCES PERFORMANCE AND JOB SATISFACTION THROUGH TRANSACTIONAL LEADERSHIP AND INTRINSIC MOTIVATION - Wuryanti, Wuryanti; Rismawan, Aldan Rifki (IJIBE (International Journal of Islamic Business Ethics), 2020)
This study aims to determine and analyze the effect of transactional leadership and intrinsic motivation on HR performance, with job satisfaction as an intervening variable. This study used primary data obtained from questionnaires. The population in this study were 155 employees of PT. SCM Enterprises Apparel who works in the production department. The research sample was 112 respondents with the cluster random sampling as a method. The results showed that transactional leadership had a positive and significant effect on HR performance, intrinsic motivation had a positive and significant effect on HR performance, job satisfaction had a positive and significant effect on HR performance, transactional leadership had a positive and significant effect on job satisfaction, intrinsic motivation had a positive and significant effect on job satisfaction, and job satisfaction cannot mediate the effect of transactional leadership and intrinsic motivation on HR performance.